Mesenchymal stem cell therapy in decompensated liver cirrhosis: a long-term follow-up analysis of the randomized controlled clinical trial - Shi, Ming; Li, Yuan-Yuan; Xu, Ruo-Nan; Meng, Fan-Ping; Yu, Shuang-Jie; Fu, Jun-Liang; Hu, Jin-Hua; Li, Jing-Xin; Wang, Li-Feng; Jin, Lei; Wang, Fu-Sheng (Hepatology international, 2021)
Background Mesenchymal stem cell (MSC) infusion was reported to improve liver function in patients with decompensated liver cirrhosis (DLC); however, whether the medication can improve outcome of these patients is poorly understood. Methods This prospective, open-labeled, randomized controlled study enrolled 219 patients with HBV-related DLC who were divided into control group ( n = 111) and umbilical cord-derived MSC (UC-MSC)-treated group ( n = 108), then all of them received a follow-up check from October 2010 to October 2017. The treated patients received three times of UC-MSC infusions at 4-week intervals plus conventional treatment that was only used for control group. The overall survival rate and HCC-free survival rate were calculated as primary endpoints and the liver function and adverse events associated with the medication were also evaluated. Results During the follow-up check period from 13 to 75th months, there was a significantly higher overall survival rate in the treated group than the control group, while the difference of the hepatocellular carcinoma event-free survival rate between the treated and control groups was not observed during the 75-month follow-up. UC-MSC treatment markedly improved liver function, as indicated by the levels of serum albumin, prothrombin activity, cholinesterase, and total bilirubin during 48 weeks of follow-up. No significant side effects or treatment-related complications were observed in the UC-MSC group. Conclusions Therapy of UC-MSC is not only well tolerated, but also significantly improves long-term survival rate, as well as the liver function in patients with HBV-related DLC. UC-MSC medication, therefore, might present a novel therapeutic approach for the disease. Graphic abstract